1994
DOI: 10.1111/j.1600-0609.1994.tb00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoreactive erythropoietin in hyper‐ and hypothyroidism: Clinical observations related to cell culture studies

Abstract: Laboratory experiments have demonstrated that tetra‐ and triiodothyronine (T4, T3) enhance hypoxia‐induced erythropoietin (Epo) production. In the present study serum immunoreactive Epo was measured in 29 patients with hyperthyroidism and in 10 patients with hypothyroidism. Epo levels were inversely correlated to the blood haemoglobin concentration [Hb] in both groups of patients. However, Epo levels at given [Hb] were significantly higher in the hyperthyroid state. In vitro studies confirmed that T4 and T3 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…This effect might be a result of the modulatory action of THs on the production of EPO. It has been demonstrated that a high concentration of THs increases the production of this hormone (10,11,25). However, in our model of in vitro cultures with an established amount of EPO given at the moment of growth induction, we observed the increased growth potential only in the samples collected from the hyperthyroid patients.…”
Section: Discussioncontrasting
confidence: 43%
“…This effect might be a result of the modulatory action of THs on the production of EPO. It has been demonstrated that a high concentration of THs increases the production of this hormone (10,11,25). However, in our model of in vitro cultures with an established amount of EPO given at the moment of growth induction, we observed the increased growth potential only in the samples collected from the hyperthyroid patients.…”
Section: Discussioncontrasting
confidence: 43%
“…Brenner et al measured serum EPO in 29 patients with hyperthyroidism and 10 patients with hypothyroidism and reported significantly higher level of EPO in the hyperthyroid group (8). Another study showed that erythropoiesis was increased in 21 patients with hyperthyroidism, and this was accompanied with an elevation in serum EPO levels (9).…”
Section: Discussionmentioning
confidence: 96%
“…ypothyroidism is a systemic disease affecting all organs [1]. Research has shown that thyroid hormone imbalance in hypothyroid patients is associated with anemia in these patients.…”
Section: Introductionmentioning
confidence: 99%